Comparison of clinical and pharmacodynamic features of proton pump inhibitors efficacy in gastroesophageal reflux disease - O. A. Storonova; A. S. Trukhmanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of review. To present literature data on clinical presentation, pharmacodynamic and economic efficiency of standard dozes of proton pump inhibitors (PPI) for gastroesophageal reflux disease (GERD).Summary. PPI are the most effective pharmaceuticals for treatment of acid-related diseases (ARD). Control of intragastric рН level is the key moment of healing of erosions and ulcers of the upper gastro-intestinal tract, as well as for Н. рylori eradication efficacy. Functional state of stomach mucosa and efficacy of antisecretory therapy was estimated by 24-hour pH or рН-impedance measurement. The standard dozes of PPI provided acid-suppressive effect for up to 18 hs. Already after the first dose intake at 24-hour рН monitoring the stomach рН>3 was recorded for 56,1% (±20,94) of total monitoring time, and рН>4 — for 44,0% (±18,72), that promoted rapid symptom relief. Terms of activation and efficacy of Н+/К+-ATPase inhibitors is determined by pH of the media and pKa values for each pharmaceutical. Intensity of acid-suppressive action of PPI depends on drug metabolic pathways and genetically determined features of cytochrome P450 system. Mutations of CYP2C19 alleles allow to divide the studied patients population into groups of rapid, mediun and slow «metabolizers» that it is necessary to take into account at prescription of the certain drug. At a choice of PPI dose or shift from one PPI to another it is necessary to be guided by the concept of equivalent dosages according to the instruction leaflet on the drug application. Long-term maintenance therapy by PPI for GERD enables reduction of expenses for treatment of disease preserving clinical efficacy.Conclusion. PPI are of the drugs of choice in ARD therapy. PPI should be applied in the least effective doze, including on demand treatment and intermittent treatment. The individual approach to PPI prescription, based on the careful analysis of clinical presentation, as well as on data of esophagogastroduodenoscopy, 24-hour pH or pH plus impedance measurement is required. Reasonable cost to efficacy ratio is no less important.